Проектирование многоступенчатых центробежных насосов на основе решения обратной и прямой гидродинамической задачи - Косторной, А. С.; Бондарев, А. О. (НТУ "ХПИ", 2014)
Обоснованная математическая модель (ММ) течения жидкости в проточной части (ПЧ) лопастной гидравлической машины (ГМ) (турбины или насоса) способствует развитию методов их проектирования и определения гидродинамических параметров для целенаправленного совершенствования энергетических, кавитационных и силовых характеристик на этапе проектирования, что значительно сокращает сроки выполнения технического задания и заменяет дорогостоящий физический эксперимент вычислительным.

High rates of the development of the chemical, coal and oil branches of industry, ferrous and non-ferrous metallurgy, power engineering and agriculture, marine and river crafts demand the advanced development of the mechanical engineering and pump mechanical engineering, which is its inseparable part. The substantiated mathematical model (MM) of the liquid flow in the flow pass (FP) of vane-type hydraulic machines (HM) (turbine and pump) contributed to the development of the methods of their design and determination of hydrodynamic parameters for the task-oriented improvement of energeric, cavitational and power characteristics at the stage of their design, which considerably reduces the time required for the fulfillment of the technical task and replaces the expensive physical experiment by the computational one.
Design of multistage centrifugal pumps on the basis of the solution of inverse and direct hydrodynamic problems
Keywords: обратная задача; прямая задача; квазипотенциальное течение; винтовое течения; inverse problem; direct problem; quasipotential flow; spiral flow